Radical Scaffolding Against Critique Fatigue - Boodman, Eva (Radical Teacher, 2019)
When using critical pedagogy in college classrooms, college students can sometimes experience critique fatigue – a despondency that results from a saturation of analysis about experiences of oppression that they experience directly. This is especially the case when there is no creative outlet for political, emotional, or practical response to the critical course material built into the classroom activities. In this essay, I exlpore the idea of using scaffolding, a pedagogical technique where students help one another perform the tasks of the course "authonomously", as a way to mitigate critique fatigue. To get around the ableism and white supremacy of its more traditional iteration, though, I propose a "radical" form of scaffolding that supports students in setting and reaching their own learning goals through creative projects that engage topics most relevant to them.